The Correlation between Blood Glucose and Lipid Profile with Skin tag - Wahyu Lestari; Sulamsih Sri Budini; Cut Yunita; Hendra Zufry; Sitti Hajar (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Skin tags or acrochordons are benign fibroepithelioma skin tumors with soft consistency, usually pedunculated, primarily originating from the dermis. High levels of blood sugar and a high lipid profile are risk factors for inflammation and hormonal imbalance, which can contribute to the development of skin tags. Purpose: The objective of this study is to identify the association between blood sugar and lipid profile with skin tags. Methods: This study is a cross-sectional study conducted from April to August 2019 at the Dermatovenereology and Endocrine Policlinic, Dr. Zainoel Abidin General Hospital, Banda Aceh. The sampling method of this study was consecutive sampling with 60 samples that met the inclusion and exclusion criteria. A blood glucose, lipid profile, and skin tag examination was conducted on all subjects. Result: The majority of the subjects are women (61.5%), have an average age of 41-50 years old (43.3%), are obese (41.7%), and have one to five lessions of 1-5 (53.3%). There was a significant correlation between blood glucose, 2 hours post-prandial, total cholesterol, triglyceride, high-density lipoprotein (HDL), and low-density lipoprotein (LDL) levels with skin tags with Spearman's correlation values of 0.645, 0.645, 0.794, 0.704, 0.606, and 0.606 consecutively. Conclusion: A high level of blood sugar and lipid profile, whether it is total cholesterol, triglycerides, HDL, or LDL level, can contribute to the development of skin tags.